Faktor-Faktor yang Memengaruhi Kepuasan Kerja dan Kinerja Karyawan di Section Assembling Body PT ABC - Dewi, Alifvina Nirmala; Wiyanto, Mukti; Widayati, Nurti; Farida, Ida (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This research aims to explain the influence of motivation, leadership, and organizational culture on job satisfaction and employee performance at assembling body section PT ABC. This sample in this research amounted to 84 employees. This research uses a non-probability sampling method with a purposive sampling technique. Data collection was carried out by distributing questionnaire containing several questions related to variables to respondents. The data analysis using structural equation modelling (SEM) with the SmartPLS version 3.0 measuring instrument. The result in this research indicate that theres a influence of motivation, leadership, and organizational culture on job satisfaction and employee performance. Also, theres a influence of job satisfaction on employee performance. Companies can create a comfortable environment, implement an appreciation system, and implement regular training to maintain and improve employee job satisfaction and performance through factors that influence both aspects.